Chiral N, N′‐Dioxide‐Organocatalyzed Regio‐, Diastereo‐ and Enantioselective Michael Addition–Alkylation Reaction. Issue 44 (30th September 2016) - Feng, Juhua; Yuan, Xiao; Luo, Weiwei; Lin, Lili; Liu, Xiaohua; Feng, Xiaoming
Abstract: A highly regio‐, diastereo‐ and enantioselective Michael addition–alkylation reaction between α‐substituted cyano ketones and ( Z )‐bromonitrostyrenes has been realized by using a chiral N, N ′‐dioxide as organocatalyst. A variety of substrates performed well in this reaction, and the corresponding multifunctionalized chiral 2, 3‐dihydrofurans were obtained in up to 95 % yield with 95:5  dr and 93 % ee . Abstract : Magic Mike : The catalytic asymmetric Michael addition/O‐alkylation reaction of ( Z )‐bromonitrostyrenes with α‐substituted cyano ketones is accomplished by using an efficient N, N ′‐dioxide organocatalyst. A range of 2, 3‐dihydrofuran derivatives is obtained with high to excellent enantiomeric excesses and excellent diastereomeric ratios.